Design of capacitive measuring systems for high frequency band sensor transducer - Arfah, Nurul; Alam, A. H. M. Zahirul; Khan, Sheroz (2010)
A 0.13-μm complementary metal-oxide-semiconductor (CMOS) technology capacitive measuring system has been proposed for detection a wide range of capacitance variation values by using less than 1.2-V supply voltage. Simulation results have successfully verified the function of the design is able to measure both small and large capacitance variations. Capacitance to Voltage Converter (CVC) system is suitable to be used in a later system of high frequency system. This converter also results to a lower power consumption with the supply voltage of ±1.2V in the circuit systems.